Fitspiration and thinspiration: a comparison across three social networking sites - Alberga, Angela S. (J Eat Disord, 2018)
BACKGROUND: Fitspiration, or images and text promoting health and fitness, and thinspiration, or images and text promoting thinness, have both received criticism for their negative effects on body image and dieting behaviors. In this study, we critically examined and compared the content of fitspiration and thinspiration on three social networking sites (SNS). METHODS: Fitspiration and thinspiration posts (N = 360) from three photo-sharing SNS (Instagram, Tumblr, and Twitter) were collected quasi-randomly on four days over two weeks. Image and associated text content were coded for variables related to weight and shape, muscularity, thin ideal, and eating. Chi-square and Fisher’s exact tests compared content of fitspiration and thinspiration posts overall and among the three SNS. RESULTS: Thinspiration images portrayed body parts more frequently than fitspiration (69.8% vs. 30.2%). Similarly, posts highlighting bony body features and references to mental illness appeared only in thinspiration. No differences were found between fitspiration and thinspiration posts with regard to sexual suggestiveness, appearance comparison, and messages encouraging restrictive eating. Fitspiration and thinspiration posts included similar images across the three SNS—focusing on appearance, sexually suggestive images, and restrictive eating—with three exceptions. Fitspiration posts exhibiting body positivity were found only on Tumblr. In thinspiration posts, references to mental illness were more frequent on Tumblr and Instagram than on Twitter, and bone emphasis was coded more frequently on Twitter than on Instagram. CONCLUSIONS: Although fitspiration posts were less extreme than thinspiration posts on the whole, notable similarities in their content support that fitspiration endorses problematic attitudes towards fitness, body image, and restrictive eating in pursuit of a fit-and-thin body ideal.